FARMING INCOME ANALISYS OF DRY LAND IN THE GUNUNGKIDUL DISTRICT (A Case Study in Prone Area Food) - Aris Slamet Widodo1, Retno Wulandari (2016)
ABSTRACT This research study was aimed at analizing the farmers’ income of local commodity in the village of Purwosari, Gunungkidul district. The study was purposively conducted in Giritirto village, Purwosari, Gunungkidul. This study used a basic method of analysis description focusing on cost analysis and farming income.The research findings show that farming frequently done by farmers in Giritirto village on rainy season is paddy and corn. While on dry season, they cultivate corn and peanut. The average income of farmers on the rainy at ricefield is higher than that at tegal land (non irigated dry field).Corn is a major commodity in the dry season and cultivated in wet land and tegal (up land). The highest income of corn is achieved at tegal land on the dry season. Peanut only planted in the dry season on dry land and is able to provide a high enough income for farmersThe analysis findings concluded that paddy commodity of ricefield has the highest income on the rainy season, while corn commodity is appropriately cultivated on the dry season at tegal land. Peanut has a quite high contribution at tegal land on the dry season.